Baby in his arms ebook - Goodnight, Linda (Whisper Falls., 2013)
A Newborn Surprise Helicopter pilot Creed Carter can't believe his eyes—someone's left a baby on the church altar. When this perfect little girl is temporarily turned over to Haley Blanchard, Creed is skeptical. The auburn-haired foster mother in flowing skirts is pretty, yet definitely not his type. But the more time Creed spends with Haley, the more he appreciates her style and her fierce commitment to her foster kids. To his surprise, he's falling for her—and for baby Rose. But when a crisis strikes, can Creed convince Haley to face her worst fear and trust what's in her heart?